Nov primerek ribe Protriacanthus gortanii D'Erasmo, 1946 (Protriacanthidae, Tetraodontiformes) iz zgornjekrednih plasti pri Komnu (Slovenija) - Križnar, Matija (Geologija, 2015)
Surroundings of Komen on Trieste-Komen Plateau are known more than two centuries as Cretaceous vertebrates site. Most frequent finds are of teleostei fishes in Komen Limestone within the Povir Formation. From platy and laminated limestone a new specimen of Protriacanthus gortanii is described. The new specimen has a characteristic morphology with strong dorsal and pelvic fin spines. The new find of Protriacanthus gortanii is probably the ninth specimen discovered so far, but it is only one with a well established stratigraphic position.
Keywords: fosili; Komen; kreda; Lake Kreda; ribe; Slovenia; Slovenija